From idea to app : creating iOS UI, animations, and gestures - Welch, Shawn (New Riders, 2011)
Because iPhone development is so young, right now apps are typically designed, developed and deployed by a single person (or very small development team.) The designers are the developers and vice versa. This book will leverage this distinction by teaching designers how to design on top of native iOS metaphors, tools and UI, while teaching native developers appropriate application design and asset preparation.